The Influence of Religious Communication and Religious Activities on Social Harmony among Buddhists at Viriya Dharma Monastery in Balerejo Village, East Lampung - Komang Yumi Arwening; Candani Kuruna Putri; Ajat Ajat; Annisa Ghina Istighfarany; Chan Phap Tu (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2026)
Social harmony is essential for maintaining cohesion and sustainable relationships within religious communities. Although religious communication is widely recognized as an important factor in promoting harmonious social interactions, the mechanisms through which it influences social harmony remain insufficiently explored, particularly in Buddhist communities. This study investigates the influence of religious communication on social harmony by examining the mediating role of understanding Buddhist teachings. An explanatory quantitative research design was employed using a questionnaire-based survey, and the data were analyzed using path analysis. The findings reveal that religious communication enhances understanding of Buddhist teachings, which subsequently strengthens social harmony. Religious communication also exerts a direct positive influence on harmonious social relationships, while understanding of Buddhist teachings serves as a significant mediating mechanism linking communication with social harmony. These findings demonstrate that effective religious communication facilitates the internalization of Buddhist values, fostering greater tolerance, solidarity, and cooperation within the community. This study contributes to the literature on religious communication by providing empirical evidence of the mediating role of doctrinal understanding in promoting social harmony and offers practical implications for strengthening communication strategies within Buddhist religious institutions.